Assessing the Impact of Higher Oil Prices in Latin America - World Bank (Washington, DC, 2012)
For some Latin American countries - especially, the oil importers in the Caribbean - rising energy prices could pose a significant threat to their current account sustainability, particularly if they are accompanied by other negative shocks. In some countries the fiscal costs associated with subsidies to protect domestic consumers have been considerable so far. Hence, a better understanding of the effects of high oil prices and potential responses in the region is needed. This report evaluates the effects of oil shocks on economic performance for a sample of selected Latin American countries. The effects at the country level depend not only on the structural characteristics of the economy, such as the degree of dependence on oil, but also on the policy reactions to rising prices. Among the countries included in our study we have: large economies (Argentina, Brazil, Colombia and Mexico), net oil exporters (Venezuela and Ecuador), and net oil importers (Dominican Republic, El Salvador, Guyana and Honduras).